Analisis Kinerja Keuangan Pada PT Bekasi Asri Pemula Tbk Periode 2014-2017 - Nenda Witama Agustin; Gesty Ernestivita; Dwi Budiadi (CAHAYA AKTIVA, 2020)
The purpose of this research is to analyze the financial performance of PT Bekasi Asri Pemula Tbk listed on the Indonesia Stock Exchange in the 2014-2017 period through the analysis of profitability, solvency, liquidity and activity ratios. The research data used are secondary data, where data is obtained indirectly from third parties or through documents. The data source of this research was obtained from the internet through the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id in the form of annual reports of property sector companies in the 2014-2017 period. The formulation of the problems in this study are (1) How was the financial performance of PT Bekasi Asri Pemula Tbk listed on the Indonesia Stock Exchange in the 2014-2017 period in terms of profitability, solvency, liquidity, activity ratios? In this study, researchers used financial research variables, namely, the ratio of profitability, solvency, liquidity, activity. Furthermore, this study uses descriptive analysis techniques using financial ratio analysis, meaning that the data obtained in the field are processedin such a way as to provide systematic, factual and accurate data regarding the problem under study.Keywords: financial performance